2014
DOI: 10.1007/s00424-014-1638-4
|View full text |Cite
|
Sign up to set email alerts
|

K2P channels in plants and animals

Abstract: Two-pore domain potassium (K2P) channels are membrane proteins widely identified in mammals, plants, and other organisms. A functional channel is a dimer with each subunit comprising two pore-forming loops and four transmembrane domains. The genome of the model plant Arabidopsis thaliana harbors five genes coding for K2P channels. Homologs of Arabidopsis K2P channels have been found in all higher plants sequenced so far. As with the K2P channels in mammals, plant K2P channels are targets of external and intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…This general architecture of the Kv channels is also shared by other S4-pore-loop/6TM1P channels (not all of them activated by voltage) with some subtle variations, including: (a) the addition of a fifth TM helix to the beginning of the VSD module in the large-conductance Ca 2+ -activated K + (BK) channel; (b) the almost total absence of positively charged residues in the S4 of some members of the family (e.g., some transient receptor potential or TRP channels); (c) the fusion of the four monomers in a single polypeptide in the voltage-gated Ca 2+ and Na + channels, where four similar repeats with six TMs mimic the tetrameric assembly of the Kv channels [4,5]. Finally, the concept of Kv channels being the result of an evolutive combination of two functionally autonomous VSD and PD modules [9,10,11] is reinforced by: (i) the existence of PD-only voltage-independent channels [12,13,14,15] that probably share a common ancestor with Kv and other voltage-dependent channels [11,16,17]; (ii) the demonstration of functional VSD-only-based voltage-dependent channels [18,19,20] and of voltage-controlled enzymes in which a VSD resembling those found in voltage-gated channels provides membrane potential control of the catalytic activity [21]; and (iii) the generation of voltage-gated ion channels by either fusing together VSDs and PDs from different sources [22,23,24], or co-expressing them as separate protein entities [25,26,27,28].…”
Section: Cryo-em: a New Catalog Of Kv And Other Ion Channel Structmentioning
confidence: 99%
“…This general architecture of the Kv channels is also shared by other S4-pore-loop/6TM1P channels (not all of them activated by voltage) with some subtle variations, including: (a) the addition of a fifth TM helix to the beginning of the VSD module in the large-conductance Ca 2+ -activated K + (BK) channel; (b) the almost total absence of positively charged residues in the S4 of some members of the family (e.g., some transient receptor potential or TRP channels); (c) the fusion of the four monomers in a single polypeptide in the voltage-gated Ca 2+ and Na + channels, where four similar repeats with six TMs mimic the tetrameric assembly of the Kv channels [4,5]. Finally, the concept of Kv channels being the result of an evolutive combination of two functionally autonomous VSD and PD modules [9,10,11] is reinforced by: (i) the existence of PD-only voltage-independent channels [12,13,14,15] that probably share a common ancestor with Kv and other voltage-dependent channels [11,16,17]; (ii) the demonstration of functional VSD-only-based voltage-dependent channels [18,19,20] and of voltage-controlled enzymes in which a VSD resembling those found in voltage-gated channels provides membrane potential control of the catalytic activity [21]; and (iii) the generation of voltage-gated ion channels by either fusing together VSDs and PDs from different sources [22,23,24], or co-expressing them as separate protein entities [25,26,27,28].…”
Section: Cryo-em: a New Catalog Of Kv And Other Ion Channel Structmentioning
confidence: 99%
“…VSD corresponds to transmembrane helices S1–S4, of which the primary voltage sensitive component is helix S4, containing the positively charged residues that move in response to changes in membrane potential [65]. The concept of Kv channels as a product of a evolutive combination of two functionally autonomous VSD and PD modules [2, 28, 69] is reinforced by (i) the existence of PD-only voltage-independent channels [8, 20, 27, 39] that probably share a common ancestor with Kv and other voltage-dependent channels [23, 29, 69], (ii) the demonstration of functional VSD-only-based voltage-dependent channels [10, 12, 54] and voltage-controlled enzymes in which a VSD resembling those found in voltage-gated channels provides membrane potential control of the catalytic activity [60] and (iii) the generation of voltage-gated ion channels by either fusing together VSDs and PDs from different sources [3, 33, 53] or co-expressing them as separate protein entities [14]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, while the activity of the Drosophila KCNK0 channel (K2P0) is enhanced by protein kinase phosphorylation (Zilberberg et al, 2000), removal of the C-terminal domain results in a channel that is insensitive to such activation (Cohen and Zilberberg, 2006;Zilberberg et al, 2000). The C-terminal domain of K2P2.1 channels was shown to be vital for regulation by phosphorylation Maingret et al, 2000), temperature (Bagriantsev et al, 2012;Maingret et al, 2000), arachidonic acid (Patel et al, 1998), internal acidification (Honore et al, 2002), internal lysophosphatidic acid (Gonzalez et al, 2015), PIP2 levels Woo et al, 2018) and mechanical stretch (Maingret et al, 1999). It was suggested that the proximal part of the Cterminal domain, which contains a charged region, is critical for chemical and mechanical activation of the channel (Patel et al, 1998).…”
Section: 4mentioning
confidence: 99%